Encapsulation-based strategies for enhanced ovarian vitrification: experimental design and research rationale - Zand, Elnaz; Zhao, Gang (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):239